The prevalence of bifid iliopsoas tendon on MRI in children - Crompton, Thomas (Springer Berlin Heidelberg, 2014)
OBJECTIVE: The variation in the anatomy of the iliopsoas tendon is important information for orthopaedic surgeons operating around the hip. The aim of this study was to identify the prevalence of bifid iliopsoas tendons in children on magnetic resonance imaging (MRI). METHODS: MRI hip and pelvis images of 50 sequential children aged 7–15 years were retrieved from our radiology database at the Evelina London Children’s Hospital from 2007 to 2013. Included were 37 children with imaging of both hips and 13 children with imaging of one hip only. Therefore, our study was based on a total of 87 hips. RESULTS: At least 1 bifid tendon was noted in 13 children (26 %). Five children from a total of 37 (14 %) with both hips adequately imaged had bilateral bifid tendons. Among all 87 adequately imaged hips, 18 (21 %) were found to have two discrete distal iliopsoas tendons. CONCLUSIONS: Bifid iliopsoas tendon is noted anecdotally by surgeons but was only reported in scattered case reports and a few anatomical studies until very recently. Our finding is that a bifid iliopsoas tendon with two distinct tendinous components at the level of the hip joint is quite common. This has clinical significance, particularly in children’s orthopaedic surgery when an adequate iliopsoas release is important.